“Efecto de tres niveles de energia en dietas alimenticias en la etapa de engorde de tilapia ( oreochromis niloticun” - Ramirez Torres, Gerlin (2002)
During a period of 90 days understood among June 01 at August of the year 2000 31; in the facilities of the Pisci Farm Demonstrative " OASIS " - Ministry of Fishery - UNSM, the effect of three energy levels was studied in nutritious diets in the productive yield of Tilapia (Oreochromis niloticus) in monocultivo, with the purpose of establishing the most appropriate energy; for it was applied it totally at random the statistical design, with three treatments of energy digestible: 2 700 food kcal/kg (T1 ), 2 900 food kcal/kg (T2) and 3 100 food kcal/kg (T3) and with two repetitions for treatment. rfhey were sowed a total of 3 600 Tilapias with a longitude total average 13, 14 cm and a peso average of 45,059. Food balanced peletizado was given, with 25 protein% twice a day. The rate of initial feeding was of 3,5% and final of 2,5% of the biomass. They were carried out biweekly biological samplings being captured a sample of 20% of fish in each experimental unit. The following averages were obtained for the treatments T1, T2, and T3, respectively: total lentitud 21,36cm; 21,48cm and 20,87; 1 weigh of 201,63g, 207,89g and 188.25, rate of specific growth of 1,74% g/día, 1,81%g/día, 1,59%g/día; Rate of survival of 89,77%, 85,75%, 91.42%; yield of 5434.75kg/ha/90días, 5317.5kg/ha/90días, 5163.25kg/ha/90 days. The results didn't show significant differences in the treatments regarding the witness.